(untitled) (Third Sector Social Economic Review, 2018)
The integration approach is not new in organizations, it emerged with the development of information technology accelerating in the second half of the 20th century, and has made very rapid progress. A successful e-business application provides competitive advantage to businesses by integrating processes at the optimum level. Management functions are also a process and the integration of this process provides a competitive advantage by minimizing the effects of uncertainty. The purpose of this research is to examine the role of e-business applications in the integration of management processes, taking advantage of the Hoshin kanri management model, which is used to reduce the effects of ambiguity (chaos and complexity approach). In other words, the purpose of this researh is to review of the literatüre of HK management cycle, which is applied to minimize the effects of variables and parameters by integrating management processes within the complex environment in which organizations operate and to make control implement with themes and phenomena which emerge the result of this literature review. In particular, the role of the control function in the integration of management processes has been identified as the primary objective in this study.